2010
DOI: 10.1002/aic.12416
|View full text |Cite
|
Sign up to set email alerts
|

Solution combustion synthesis of metal nanopowders: Nickel—Reaction pathways

Abstract: Wiley Online Library (wileyonlinelibrary.com).Nanopowders of pure nickel were directly synthesized for the first time by conventional solution combustion synthesis (SCS) method. In this article, a specific reaction pathway is suggested to describe the metallic phase formation during SCS. It is proposed that the exothermic reaction between NH 3 and HNO 3 species formed during the decomposition of glycine and nickel nitrate acts as the source of energy required to achieve the self-sustained reaction regime. A th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 22 publications
6
90
0
Order By: Relevance
“…10,11 However, these approaches are generally multisteps and time consuming, requiring pre/ posttreatments such as separation, washing or annealing to improve purity and crystallinity. Flexible control over composition, structure, and particle size during these processes is difficult to achieve, with the mechanisms poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, these approaches are generally multisteps and time consuming, requiring pre/ posttreatments such as separation, washing or annealing to improve purity and crystallinity. Flexible control over composition, structure, and particle size during these processes is difficult to achieve, with the mechanisms poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion synthesis (CS) techniques, being simple, quick and economic processes, are being used for synthesizing nanoparticles for various applications such as catalysis, drug delivery, magnetic materials etc [1][2][3][4][5][6][7][8]. These CS methods can be categorized in different groups on the basis of the nature of the reaction media as: (i) flame synthesis, (ii) heterogeneous condensed phase synthesis and (iii) solution-combustion synthesis (SCS).…”
Section: Introductionmentioning
confidence: 99%
“…These CS methods can be categorized in different groups on the basis of the nature of the reaction media as: (i) flame synthesis, (ii) heterogeneous condensed phase synthesis and (iii) solution-combustion synthesis (SCS). The SCS method uses water soluble precursor materials to make a homogeneous solution producing molecular level mixing, which results in a uniform product after combustion and provides an easy one step route for synthesizing metal/oxide nanoparticles [2,5,6,11]. The SCS method uses water soluble precursor materials to make a homogeneous solution producing molecular level mixing, which results in a uniform product after combustion and provides an easy one step route for synthesizing metal/oxide nanoparticles [2,5,6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors 7 have suggested hydrogen coming from the glycine as the main reducing agent even though the pyrolysis of amino acids usually leads to NH 3 , CO 2 and water. 15 The ratio of glycine to nitrate ions is of great relevance as the lean fuel compositions do not ignite and other glycine rich stoichiometries do not provide the vigorous reaction to produce the metal phase.…”
Section: Journal Of the Electrochemicalmentioning
confidence: 99%
“…The synthesis of metallic nickel by combustion synthesis has been reported to take place in a hot-plate 6 and an insight into the reaction mechanism has been given before. 7 Previous reports indicate the production of nickel metal by irradiating with microwaves a mixture of nickel nitrate and an organic fuel [8][9][10] with reaction times up to 10 minutes. Here, we take the experiments further by simplifying and speeding up the synthesis and using it as a processing technique with great potential to produce anodes for fuel cells.…”
mentioning
confidence: 99%